ReQuest in the Secondary History Classroom: How does the Introduction of a Purposeful Reading Technique Effect Comprehension of Text? - Jeffery Peleaux; Jason Endacott (Networks: An Online Journal for Teacher Research, 2013)
This quantitative, action research study sought to explore the effects of introducing the ReQuest reading comprehension technique to students who are accustomed to using a world history textbook and the initiate-respond-evaluate questioning pattern to acquire basic historical information. Data collected from a series of paired sample quiz scores indicates that the ReQuest method shows promise as part of a purposeful, reciprocal teaching method when reading comprehension of expository text is the explicit goal of the classroom teacher. The results of this exploratory study support the literature on the use of explicitly taught reading strategies and suggests that further investigation of the ReQuest technique in the social studies classroom is warranted.